Mechanisms governing the pioneering and redistribution capabilities of the non-classical pioneer PU.1 - Julia Minderjahn; Andreas Schmidt; Andreas Fuchs; Rudolf Schill; Johanna Raithel; Magda Babina; Christian Schmidl; Claudia Gebhard; Sandra Schmidhofer; Karina Mendes; Anna Ratermann; Dagmar Glatz; et al. (Nature Communications, 2020)
PU.1 is a master TF of hematopoietic lineage differentiation. Here the authors analyse properties of PU.1 DNA-binding in vitro and genome-wide in vivo across different cell types with native or ectopic PU.1 expression, and uncover the mechanisms governing the pioneering and redistribution capabilities of the non-classical pioneer PU.1.